Daddy : Daddy - Ayeah, Colin Diyen (Book collections on Project MUSE., 2014)
Men who are Senior Citizens can be quite interesting. There are quite a few who are tired and simply want to enjoy a deserved rest by the side of their old wives. There are others who still have much energy and want to remain very active. The worst among these are those who spent their youth deprived of any form of excitement. This could have been either because they lacked the opportunities, or were too shy and withdrawn to look for fun. Now, with the funds available and women at their disposal, they insist on catching up with lost time. Daddy is a hilarious book for old men and women. However, since all the young men and women of today will grow old someday, they should have a go at having an exciting life and prepare themselves to best enjoy the escapades of men who are on the leeward side of life.